Analysis of an iron-core and ironless railguns powered sequentially. Issue 5 (17th August 2018) - Waindok, Andrzej; Piekielny, Pawel
Abstract : Purpose: The purpose of this paper is to calculate and measure transients for two different constructions of electrodynamic accelerators (ironless and iron-core) supplied by a three-section power system (three capacitor banks). The optimization of power supply parameters (switch-on times and capacitances of individual sections) in terms of system efficiency has been carried out. Design/methodology/approach: Calculations have been carried out using a field-circuit model. For three-dimensional magnetostatic analysis, the Maxwell software and finite element method (FEM) were used, while for circuit model, the Matlab/Simulink software was implemented. For optimization of the supply system parameters, the genetic algorithm was used. The mathematical models were verified experimentally by using the original laboratory stand. Findings: The efficiency of the system is much higher in case of iron-core accelerator. In both cases, the results obtained for optimized supply settings are only slightly better than those obtained by simultaneously switching on the thyristors and for symmetrical capacity division. Research limitations/implications: Due to the presented field-circuit model, eddy currents in rails have been neglected. In the field model, there was no possibility to combine current flow calculations with moving of the projectile. Originality/value: Using the presented filed-circuit model, both electrical and mechanical transients could be calculated with sufficient precision. Thus, it could be used in the optimization of supply system. The solution time is low compared with the solution time of the transient field model.